1989
DOI: 10.1007/bf00218895
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a monoclonal antibody directed against a sulphoglycolipid that is evolutionarily conserved and developmentally regulated in rat brain

Abstract: Summary. Monoclonal antibodies (MABs) have been raised against acidic glycolipids extracted from the electric organ of Torpedo marmorata. One of these, designated L9, appears to recognize acidic glycolipids in adult T. marmorata electric organ, electromotor nerves and brain, adult rat sciatic nerve, and in embryonic and neonatal rat brain, starting at embryonic day (ED) 15 and disappearing by the 20th day of post-natal life. The epitope is present in growth cones isolated from 4-day-old rats; its proportion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The total cellular distribution of the HNK-1 epitope in the electric organ reflects that of a variety of glycoproteins (including acetylcholinesterase and 5'-nucleotidase) and glycolipids (Borroni et al, 1989). In spite of this, the pattern of antibody binding revealed by immunocytochemistry corresponds closely to that previously observed for 5'-nucleotidase (Grondal & Zimmermann, 1987;Grondal et al, 1988).…”
Section: Discussionsupporting
confidence: 72%
“…The total cellular distribution of the HNK-1 epitope in the electric organ reflects that of a variety of glycoproteins (including acetylcholinesterase and 5'-nucleotidase) and glycolipids (Borroni et al, 1989). In spite of this, the pattern of antibody binding revealed by immunocytochemistry corresponds closely to that previously observed for 5'-nucleotidase (Grondal & Zimmermann, 1987;Grondal et al, 1988).…”
Section: Discussionsupporting
confidence: 72%
“…Since there is some structural resemblance between the glucuronic acid-containing glycosphingolipids, the arthrosides, of insects, and the sialic acid-containing gangliosides of vertebrates, it is tempting to speculate that glucuronic acid and sialic acid are of similar biological significance in these two groups of acidic glycolipids. And it might be taken in a support of such a hypothesis that glucuronic acidcontaining glycolipids are indeed also present in the mammalian peripheral nervous system, being also detected as developmentally regulated molecules of the embryonic and neonatal brain [41,44,45]. A preliminary immunohistochemical study using MAb CAF-I has demonstrated that glycoconjugates, that are recognized by this antibody, were differentially expressed at different stages of central nervous system development of the dipteran Ç_^v icina and coleopteran Tenebrio molitor [20] .…”
Section: Discussionmentioning
confidence: 92%
“…This epitope is present on both, vertebrate glycoproteins and glycolipids. Thus, HNK-1 reacted with a surface antigen on human natural killer cells [39], L2 with glycoproteins from embryonal mouse brain [40], and L9 with acidic glycolipids of the electric organ of Torpedo marmorata [41]. In addition, some patients with an autoallergic demyelinating peripheral neuropathy produced a monoclonal IgM Mprotein that also recognized a sulphated glucuronic acid containing epitope [42].…”
Section: Discussionmentioning
confidence: 99%